2015
DOI: 10.5603/kp.a2014.0237
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of aspirin resistance and the presence of unstable carotid plaque in patients undergoing carotid endarterectomy

Abstract: 1. Prevalence of increased platelet reactivity despite ASA treatment (ASA resistance) in patients treated surgically for carotid artery disease is high, suggesting a possibility of ineffective antiplatelet therapy. 2. A modest correlation between abnormal platelet response during treatment with ASA and the presence of unstable plaques suggests that these two phenomena may coexist but we were unable to show a clear association between them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, some patients show resistance to clopidogrel or aspirin and impaired inhibition of platelet aggregation 12. It has been estimated that 4.2–31.0% of patients treated with clopidogrel do not achieve an appropriate level of efficacy of platelet activity,13–15 and aspirin resistance accounts for 7.8–32.0% of patients with recurrent events 16 17. Many platelet function tests have been used to define the responsiveness of patients with cardiovascular disease to clopidogrel or aspirin 16.…”
Section: Discussionmentioning
confidence: 99%
“…However, some patients show resistance to clopidogrel or aspirin and impaired inhibition of platelet aggregation 12. It has been estimated that 4.2–31.0% of patients treated with clopidogrel do not achieve an appropriate level of efficacy of platelet activity,13–15 and aspirin resistance accounts for 7.8–32.0% of patients with recurrent events 16 17. Many platelet function tests have been used to define the responsiveness of patients with cardiovascular disease to clopidogrel or aspirin 16.…”
Section: Discussionmentioning
confidence: 99%
“…37 In addition, a study of 66 patients taking 75 mg of aspirin monotherapy in the preoperative and perioperative period found that there was a possible correlation (P ¼ .051) between AR (32% of patients) and the presence of unstable carotid artery plaques at carotid endarterectomy. 36 Several studies have identified a transient AR in the perioperative period. A study of platelet response to AA in patients taking aspirin immediately before and immediately after carotid endarterectomy revealed a 570% increase in platelet aggregation to AA after the procedure compared with the low AA response before surgery, with no additional intake of aspirin.…”
Section: Ar In Padmentioning
confidence: 99%
“…Temporary postoperative ASA nonresponse is clinically relevant since it may influence the rate of thromboembolic complications. [19][20][21] Lewszuk et al 21 investigated 66 patients who underwent a carotid endarterectomy and were pre-treated with ASA 75 mg/d. They measured platelet aggregation with the analyzer PFA-100 on the second day after the operation and identified a nonresponder rate of 32% (19 out of 66 patients).…”
Section: Discussionmentioning
confidence: 99%
“…Lewszuk et al 21 investigated 66 patients who underwent a carotid endarterectomy and were pre-treated with ASA 75 mg/d. They measured platelet aggregation with the analyzer PFA-100 on the second day after the operation and identified a nonresponder rate of 32% (19 out of 66 patients).…”
Section: Discussionmentioning
confidence: 99%